GAMBARAN TINGKAT DEPRESI MAHASISWA DAN FAKTOR PENYEBAB DEPRESI MAHASISWA TINGKAT AKHIR DI UNIVERSITAS RIAU - Laoli, Siska Erni Wandayani; Nauli, Fathra Annis; Karim, Darwin (Coping: Community of Publishing in Nursing; Vol 10 No 1 (2022): Februari 2022DO - 10.24843/coping.2022.v10.i01.p15, 2022)
The demands of working on this thesis make the thesis one of the causes of depression in final year students. Factors causing depression consist of three factors, namely biological factors, genetic factors, and psychosocial factors. The purpose of this study was to describe the level of depression in students and the factors causing depression in final year students at the University of Riau. The research method used is quantitative with a descriptive research design. The research sample was 369 final year students from 10 faculties at the University of Riau using stratified random sampling technique. The measuring instrument used was a depression level questionnaire which was modified from the Beck Depression Inventory II and Thesis Stress Factor. The results showed that the majority of final year students experienced moderate depression (35,0%). Factors cause depression in final year students consist of anxiety factors are 76,2%, delaying factors are 69,9%, unable to prioritize thesis factors as much as 68,6%, time management factors are 64,5%, parents pressure factors 58,5%, 56,6% economic factor, 56,1% difficulty finding references, 55,6% laziness factor, 54,7% difficulty expressing thoughts, 53,9% academic factor, the thesis disinterest factor is 28,7%. The results of this study recommend to final year students to add information and add insight about the level of depression and the factors that cause depression that affect it and can prevent it.